2008
DOI: 10.1165/rcmb.2007-0322oc
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 Promoter Hypermethylation

Abstract: Mechanisms regulating myofibroblastic differentiation of fibroblasts within fibroblastic foci in idiopathic pulmonary fibrosis (IPF) remain unclear. Epigenetic processes, including DNA methylation, produce heritable but potentially reversible changes in DNA or its associated proteins and are prominent in development and oncogenesis. We have shown that Thy-1 suppresses myofibroblastic differentiation of lung fibroblasts and that fibroblasts in fibroblastic foci are Thy-1(2). Epigenetic down-regulation of Thy-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(110 citation statements)
references
References 40 publications
3
106
0
1
Order By: Relevance
“…HumanMethylation27 array) [16]. Studies of specific genes – namely, Thy-1 [19], PTGER2 [18], and p14 ARF [17] – have identified their differential methylation in IPF fibroblasts, but this is the first study of which we are aware that describes genome-wide differences in DNA methylation in these critical mesenchymal effector cells.…”
Section: Discussionmentioning
confidence: 98%
“…HumanMethylation27 array) [16]. Studies of specific genes – namely, Thy-1 [19], PTGER2 [18], and p14 ARF [17] – have identified their differential methylation in IPF fibroblasts, but this is the first study of which we are aware that describes genome-wide differences in DNA methylation in these critical mesenchymal effector cells.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Thy-1 (CD90) is an important regulator of cell–cell and cell– matrix interactions that is expressed on normal lung fibroblasts but its expression is absent in myofibroblasts within fibroblastic foci (FF) in IPF. Thy-1 downregulation in rat lung fibroblasts is controlled by both promoter DNA hypermethylation [102] and histone modifications [103]. Thy-1 hypermethylation and dowregulation of expression have also been observed in human lung fibroblasts as a result of hypoxia [104].…”
Section: Epigenetic Studies In Ipfmentioning
confidence: 99%
“…Several targeted studies have shown that epigenetic modulation (both DNA methylation and histone marks) regulates expression of genes and miRNAs involved in pathogenesis of IPF (Table 1), namely, cyclooxygenase-2 (COX2) (92, 93), chemokine IP-10 (94), Thy-1 (CD90) (95, 96), p14(ARF) (97), α-smooth muscle actin (α-SMA) (98, 99), and miR-17~92 cluster (100). Similarly, molecular processes of high relevance to pulmonary fibrosis are also epigenetically regulated; this has been demonstrated specifically for fibroblast apoptosis (101, 102), cell senescence (103), and innate immunity (104) in IPF.…”
Section: Targeted Studies Of Dna Methylation and Histone Modificationmentioning
confidence: 99%